THE ROLE OF MOSQUES IN MSME DEVELOPMENT IN MEDAN CITY - Khairunnisa Khairunnisa; Siti Ardila Siregar (Proceeding International Seminar of Islamic Studies, 2022)
Mosques play a strategic role in the development of civilization for Muslims. During the reign of the Prophet, the mosque became the center of policymaking. In addition, during the heyday of Islam in the light period, the mosque became a center for education, politics, and socio-economics. However, the role of the mosque seems to be narrowed, only as a place of worship rituals. Therefore, this study aims to examine the function of mosques that can develop MSMEs that operate around the mosque. According to data from the Central Statistics Agency (BPS) in 2018, the number of MSMEs reached 64.2 million units, where MSME business activities contributed 99.9% of all businesses operating in Indonesia. Currently, the number of MSMEs registered with the Medan City MSME Service is 773. This study examines the role of three mosques in Medan City, which were identified as having BMTs for the congregation's welfare and collaborating with surrounding MSMEs. The method used in this study is a descriptive qualitative method carried out at the Al-Falaah Raya Mosque, Nurul Yaqin Mosque, and Taqwa Muhammadiyah Mosque Kp. Dadap. As for the study results, it was found that traders felt helped because the mosque did not charge fees for those who sold in the mosque environment and felt the impact when there was a recitation event or a big day held at the mosque. Surrounding communities who are in the poor category are also given regular infaq and alms for primary needs. Masjid Al - Falah Raya also collaborates with entrepreneurs to make coffee products called mosque coffee. Nevertheless, many potentials can be maximized by the mosque to support MSMEs in the city of Medan..Keywords: MSME, Mosque Management, Community Development